S100A8/9 modulates perturbation and glycolysis of macrophages in allergic asthma mice - Ji, Xiaoyi; Nie, Chunhua; Yao, Yuan; Ma, Yu; Huang, Huafei; Hao, Chuangli (PeerJ, 2024)
Background Allergic asthma is the most prevalent asthma phenotype and is associated with the disorders of immune cells and glycolysis. Macrophages are the most common type of immune cells in the lungs. Calprotectin (S100A8 and S100A9) are two pro-inflammatory molecules that target the Toll-like receptor 4 (TLR4) and are substantially increased in the serum of patients with severe asthma. This study aimed to determine the effects of S100A8/A9 on macrophage polarization and glycolysis associated with allergic asthma. Methods To better understand the roles of S100A8 and S100A9 in the pathogenesis of allergic asthma, we used ovalbumin (OVA)-induced MH-S cells, and OVA-sensitized and challenged mouse models (wild-type male BALB/c mice). Enzyme-linked immunosorbent assay, quantitative real-time polymerase chain reaction, flow cytometry, hematoxylin-eosin staining, and western blotting were performed. The glycolysis inhibitor 3-bromopyruvate (3-BP) was used to observe changes in glycolysis in mice. Results We found knockdown of S100A8 or S100A9 in OVA-induced MH-S cells inhibited inflammatory cytokines, macrophage polarization biomarker expression, and pyroptosis cell proportion, but increased anti-inflammatory cytokine interleukin (IL)-10 mRNA; also, glycolysis was inhibited, as evidenced by decreased lactate and key enzyme expression; especially, knockdown of S100A8 or S100A9 inhibited the activity of TLR4/myeloid differentiation primary response gene 88 (MyD88)/Nuclear factor kappa-B (NF-κB) signaling pathway. Intervention with lipopolysaccharides (LPS) abolished the beneficial effects of S100A8 and S100A9 knockdown. The observation of OVA-sensitized and challenged mice showed that S100A8 or S100A9 knockdown promoted respiratory function, improved lung injury, and inhibited inflammation; knockdown of S100A8 or S100A9 also suppressed macrophage polarization, glycolysis levels, and activation of the TLR4/MyD88/NF-κB signaling pathway in the lung. Conversely, S100A9 overexpression exacerbated lung injury and inflammation, promoting macrophage polarization and glycolysis, which were antagonized by the glycolysis inhibitor 3-BP. Conclusion S100A8 and S100A9 play critical roles in allergic asthma pathogenesis by promoting macrophage perturbation and glycolysis through the TLR4/MyD88/NF-κB signaling pathway. Inhibition of S100A8 and S100A9 may be a potential therapeutic strategy for allergic asthma.
Keywords: Allergic asthma; S100A8/9; Glycolysis; Macrophages perturbation; TLR4/MyD88/NF-κB